Perception and self-management of hypertension in Chinese cardiologists (CCHS): a multicenter, large-scale cross-sectional study. Issue 9 (27th September 2019) - Hou, Lei; Jin, Xuejuan; Ma, Jianying; Qian, Juying; Huo, Yong; Ge, Junbo
Abstract : Objectives: To determine the frequency of risk factors for hypertension among Chinese cardiologists using a nation-wide survey. Design: Multicenter, cross-sectional observational study. Setting: 2441 hospitals across China were surveyed between September 2016 and August 2017. Participants: All in-service cardiologists were surveyed (n=28 924). Interventions: WeChat-based electronic data capture system, a social application in China (Tencent, Nanshan, China), was used for data acquisition. Physician subscribed to the WeChat official account of the China Cardiologist Heart Study, and filled out an online questionnaire that included age, gender, level of in-service hospital, professional title, academic degree, area of expertise and cardiovascular risk factors. All information was required. Primary and secondary outcome measures: The primary outcome was the presence of cardiovascular risk factors. The secondary outcome was the impact of the risk factors on the occurrence of hypertension. Results: Among 28 924 Chinese cardiologists who completed the questionnaire, 57.6% had blood pressure of 130–139/80–89 mm Hg (5.3% were taking antihypertensive drugs) and 22.0% had blood pressure > 140/> 90 mm Hg (36.5% were taking antihypertensive drugs). The multivariable analysis showed that age, gender, academic degree, hospital level, body mass index (BMI), smoking and comorbidities were independently associated with hypertension among cardiologists (all p<0.05). Age, female gender, BMI, smoking, family history of cardiovascular diseases (CVDs) and comorbidities were independently associated with taking antihypertensive drugs among hypertensive cardiologists (all p<0.05). Age, hospital level, professional title, BMI, family history of CVDs and comorbidities were independently associated with reaching target blood pressure among hypertensive cardiologists taking antihypertensive drugs. Conclusion: Chinese cardiologists do not recognise and pay attention to their own blood pressure. Their rate of antihypertensive treatment was low. The identified risk factors could be used to identify cardiologists at higher risk for hypertension and for implementing preventive interventions.